Treatment method for modifying surface of silver powder
The method forms chemical bonds between nano and main silver powders using specific solvents and compounds to address agglomeration and uneven distribution issues, enhancing conductivity and mechanical properties of silver paste for solar cells.
Patent Information
- Application Number
- CN202411246580.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-13
AI Technical Summary
Existing methods for surface modification of silver powder, such as direct mixing, solvent impregnation, and electrodeposition, face issues like agglomeration, uneven distribution, high production costs, and equipment complexity, making it difficult to ensure quality and performance.
A method involving the formation of chemical bonds between nano silver powder and main silver powder using specific organic solvents and compounds, including low and high boiling point alcoholamines and carboxylic acids, followed by ultrasonic dispersion and mechanical mixing, to achieve uniform dispersion and stable loading.
The method ensures high uniformity and stability of nano silver powder distribution, reducing agglomeration and enhancing conductivity and mechanical properties, thereby improving the performance of silver paste used in solar cells.
Smart Images

Figure CN119114935A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal powders, and in particular relates to a treatment method for surface modification of silver powder. Background Art
[0002] At present, silver paste is widely used in the photovoltaic industry, mainly in the manufacturing process of solar cells. Silver paste is used as a conductive material for electrodes in the manufacture of solar cells. It can effectively conduct current and has good oxidation resistance and stability. These properties are very important for the long-term stable operation of solar cells.
[0003] Silver powder is the main component of silver paste. Its quality and characteristics will directly affect the conductivity, oxidation resistance and other physical and chemical properties of silver paste. Therefore, choosing the right silver powder is crucial to the preparation of efficient and reliable silver paste.
[0004] The conductivity of silver paste depends on the sintering characteristics of silver powder. Sintered silver powder has excellent conductivity because silver ions achieve good electronic conduction through direct contact or the formation of tiny silver bridges during the sintering process. During the sintering process of silver powder, the gaps between particles will decrease, which will eventually affect the density of the product. The sintering density and porosity have a significant impact on the electrical and mechanical properties of silver powder. The ideal sintered silver powder should have a lower porosity to enhance its performance.
[0005] At present, there are the following ways to improve the sintering activity of silver powder: controlling the shape of silver powder particles, surface modification of silver powder, optimizing the sintering process of silver powder, etc. Taking the surface modification of silver powder as an example, the existing technology generally uses direct mixing, solvent impregnation, electrodeposition and other methods to process nano silver powder. However, when adding nano silver powder to the main silver powder, the direct mixing method will cause the nano silver powder to agglomerate due to factors such as van der Waals force, affecting the dispersion and performance of the final silver powder; the solvent impregnation method is difficult to control the penetration depth of the nano silver powder in the main silver powder, which may lead to uneven distribution, and the substrate size may change during the drying process, affecting the product quality and stability; the electrodeposition method requires complex equipment and special electrochemical equipment, which increases production costs, and multiple depositions may cause the electrode surface to be contaminated by nano particles, and requires precise control of voltage and current. If the operation is not careful, it may cause electrode damage or product quality problems.
[0006] It can be seen that the existing methods for surface modification of silver powder still have many restrictions, and the operation is cumbersome but it is difficult to ensure the quality. Therefore, it is necessary to propose a simple and efficient method to solve the above problems. Summary of the invention
[0007] In order to solve the above technical problems, the purpose of the present invention is to provide a treatment method for surface modification of silver powder, which realizes surface modification of the main silver powder by reacting organic matter on the surface of nano silver powder with organic matter on the surface of main silver powder to form chemical bonds. The method has the advantages of large processing capacity, simple operation, high uniform dispersion, stable yield and excellent performance.
[0008] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:
[0009] A method for surface modification of silver powder, comprising the following steps:
[0010] (1) mixing a first low boiling point solvent with a high boiling point alcoholamine compound to form a first organic solvent, and mixing a second low boiling point solvent with a high boiling point carboxylic acid compound to form a second organic solution;
[0011] (2) mixing the first organic solvent with the nano silver powder and performing ultrasonic dispersion to form a nano silver paste;
[0012] (3) mixing the second organic solvent with the main silver powder so that the surface of the main silver powder is wetted by the second organic solvent;
[0013] (4) mixing the nano silver paste and the wetted main silver powder evenly to obtain a mixed silver paste;
[0014] (5) Drying the mixed silver paste to obtain surface-modified silver powder.
[0015] Preferably, in the first organic solvent, the first low boiling point solvent is an organic solvent having a boiling point of 50 to 100° C., and the boiling point of the alcoholamine compound is 150 to 200° C.;
[0016] The mass ratio of the first low boiling point solvent to the alcohol amine compound is (0.2-0.8):1.
[0017] More preferably, the first low boiling point solvent includes one or more of n-hexane, triethylamine, methanol and acetone.
[0018] More preferably, the alcoholamine compound includes one or more of ethanolamine, isopropanolamine, N-methylethanolamine and aminomethylpropanol.
[0019] Preferably, in step (2), the mass ratio of nano silver powder to nano silver paste is (0.6-0.8):1.
[0020] Preferably, in the second organic solvent, the second low boiling point solvent is an organic solvent with a boiling point of 100 to 200°C, the boiling point of the carboxylic acid compound is 140 to 300°C, and more preferably, the boiling point of the carboxylic acid compound is 200 to 300°C;
[0021] The mass ratio of the second low boiling point solvent to the carboxylic acid compound is (0.2-0.8):1.
[0022] More preferably, the second low boiling point solvent includes one or more of phorone, cyclohexanone and ethylene glycol.
[0023] More preferably, the carboxylic acid compound includes one or more of acrylic acid, n-octanoic acid, linoleic acid and caproic acid.
[0024] Preferably, in step (3), the main silver powder is silver powder with a D50 particle size of 1 to 2 μm.
[0025] Preferably, the mass ratio of the second organic solvent to the main silver powder is (0.001-0.05):1.
[0026] Beneficial effects:
[0027] The present invention adopts the form of forming chemical bonds to load the nano silver powder on the surface of the main silver powder. In the process of mixing the nano silver powder and the main silver powder, due to the tendency of generating chemical bonds, the nano silver powder is more likely to enter the gap of the main silver powder. During the subsequent contact, the alcohol amine compound on the surface of the nano silver powder contacts and condenses with the carboxylic acid compound on the surface of the main silver powder to generate a peptide bond, thereby maintaining the stable loading of the nano silver powder on the surface of the main silver powder. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The following are SEM (50.0K) images of the nano-silver powder used in the embodiments and comparative examples.
[0029] Figure 2 This is the SEM (50.K) photograph of the untreated main silver powder raw material.
[0030] Figure 3 This is a SEM (50.0K) photograph of the silver powder after the mixing treatment in Example 1.
[0031] Figure 4 This is a TMA thermal analysis comparison curve of the main silver powder before treatment and the main silver powder after treatment in Example 1. DETAILED DESCRIPTION
[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the specific implementation methods of the present invention will be described below with reference to the accompanying drawings. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings and other implementation methods can be obtained based on these drawings without creative work.
[0033] The present invention provides a treatment method for surface modification of silver powder, which modifies the main silver powder in a simple and efficient manner, improves product quality and reduces operation difficulty. The specific steps are as follows:
[0034] (1) mixing a first low boiling point solvent with a high boiling point alcoholamine compound to form a first organic solvent, and mixing a second low boiling point solvent with a high boiling point carboxylic acid compound to form a second organic solution;
[0035] (2) mixing the first organic solvent with the nano silver powder and performing ultrasonic dispersion to form a nano silver paste;
[0036] (3) mixing the second organic solvent with the main silver powder so that the surface of the main silver powder is wetted by the second organic solvent;
[0037] (4) uniformly mixing the nano silver paste with the wetted main silver powder to obtain a mixed silver paste, wherein during the mixing process, the alcohol amine compound in the first organic solvent and the carboxylic acid compound in the second organic solvent preliminarily react to cause the nano silver powder particles to be embedded in the gaps of the main silver powder;
[0038] (5) drying the mixed silver paste to accelerate the reaction of the alcoholamine compound and the carboxylic acid compound, so that the nano silver powder is evenly embedded in the gaps of the main silver powder, and finally the nano silver powder is loaded on the surface of the main silver powder to obtain surface modified silver powder.
[0039] The present invention innovatively adopts the form of chemical bonds to load the nano silver powder on the surface of the main silver powder. During the mixing process of the nano silver powder and the main silver powder, due to the tendency of generating chemical bonds, the nano silver powder is more likely to enter the gaps of the main silver powder. During the subsequent contact, the alcohol amine compound on the surface of the nano silver powder contacts and condenses with the carboxylic acid compound on the surface of the main silver powder to generate peptide bonds, so that the nano silver powder is stably loaded on the surface of the main silver powder.
[0040] In step (1), the first organic solvent and the second organic solvent are both low-boiling point solvents mixed with alcoholamine compounds or carboxylic acid compounds. The viscosity of the high-boiling point alcoholamine compounds or carboxylic acid compounds used in the present invention is relatively high. The role of the low-boiling point solvent is to dilute the alcoholamine compounds and carboxylic acid compounds so that the alcoholamine compounds and carboxylic acid compounds are better coated on the surface of the corresponding silver powder. It is easy to understand that the reaction of the alcoholamine compound and the carboxylic acid compound is the key to uniform mixing of the nano silver powder and the main silver powder. The first low-boiling point solvent should avoid reacting with the alcoholamine compound and the carboxylic acid compound. Similarly, the second low-boiling point solvent should avoid reacting with the alcoholamine compound and the carboxylic acid compound.
[0041] The first low boiling point solvent and the second low boiling point solvent are preferentially dried out in step (5).
[0042] Preferably, in step (1), the first low boiling point solvent is an organic solvent having a boiling point of 50 to 100° C. It is easy to understand that low boiling point organic solvents that do not react with alcohol amine compounds, carboxylic acid compounds and the second low boiling point solvent are suitable for the present invention. More preferably, the first low boiling point solvent includes one or more of n-hexane, triethylamine, methanol and acetone.
[0043] Preferably, in step (1), the boiling point of the alcoholamine compound is 150-200° C., such as one or more of ethanolamine, isopropanolamine, N-methylethanolamine (ie, methylethanolamine) and aminomethylpropanol (ie, isobutanolamine).
[0044] In the first low boiling point solvent and the alcohol amine compound, "low boiling point" means that the boiling point of the first low boiling point solvent is lower than that of the alcohol amine compound. Similarly, "high boiling point" means that the boiling point of the alcohol amine compound is higher than that of the first low boiling point solvent.
[0045] In the first organic solvent, the mass ratio of the first low boiling point solvent to the alcoholamine compound is (0.2-0.8):1.
[0046] In step (2), the mass ratio of nano silver powder to nano silver paste is (0.6-0.8):1, that is, the solid content of the nano silver paste is 60-80%.
[0047] In step (2), the first organic solvent is mixed with the nano silver powder, and then kept warm in a water bath at 15-35° C., and ultrasonically dispersed uniformly.
[0048] Preferably, in step (1), the second low boiling point solvent is an organic solvent having a boiling point of 100 to 200° C. It is easy to understand that low boiling point organic solvents that do not react with the alcoholamine compound, the carboxylic acid compound and the first low boiling point solvent are suitable for the present invention. More preferably, the second low boiling point solvent includes one or more of phorone, cyclohexanone and ethylene glycol.
[0049] Preferably, in step (1), the boiling point of the carboxylic acid compound is 140-300°C, such as one or more of acrylic acid, n-octanoic acid, linoleic acid and caproic acid. More preferably, the boiling point of the carboxylic acid compound is 200-300°C.
[0050] In the second low boiling point solvent and the carboxylic acid compound, "low boiling point" means that the boiling point of the second low boiling point solvent is lower than that of the carboxylic acid compound. Similarly, "high boiling point" means that the boiling point of the carboxylic acid compound is higher than that of the second low boiling point solvent.
[0051] In the second organic solvent, the mass ratio of the second low boiling point solvent to the carboxylic acid compound is (0.2-0.8):1.
[0052] In step (3), the main silver powder preferably has a D50 particle size of 1 to 2 μm. The mass ratio of the second organic solvent to the main silver powder is (0.001 to 0.05):1. The second organic solvent acts as a wetting agent, and its usage is relatively small, as long as the surface of the main silver powder is wetted.
[0053] In step (4), a planetary centrifuge can be used to evenly mix the nano silver paste with the wetted main silver powder. Specifically, the working stages are set to five sections, and the mixing speed is increased successively. For example, the mixing speeds of the five working stages are 400 rpm, 800 rpm, 1000 rpm, 1200 rpm and 1400 rpm respectively.
[0054] In step (4), the mass ratio of the nano silver powder to the main silver powder is ≤5% to avoid affecting the tap density.
[0055] In step (5), the drying temperature is ≤50° C. In step (4), the condensation reaction has already occurred. Since the condensation reaction between the amino group and the carboxyl group is an exothermic reaction, the low-boiling point solvent can be volatilized. In step (5), the drying temperature does not need to be too high, and it is sufficient to ensure that the low-boiling point solvent is completely volatilized. In addition, the drying step provides a suitable temperature for the condensation reaction to promote the reaction to continue.
[0056] Preferably, the drying time is 60 to 120 minutes.
[0057] The invention combines ultrasonic mixing, mechanical mixing and solvent impregnation, and adopts a special organic solvent to coat the nano silver powder and the main silver powder respectively. Through the reaction of the alcohol amine compound and the carboxylic acid compound, the nano particles are evenly dispersed among the main silver powder without agglomeration. The control process is controllable, the use of equipment is simple and direct, and the processing cost is low.
[0058] The technical solution of the present invention is described in detail below with specific embodiments.
[0059] Example 1
[0060] 1.0 g of n-hexane and 3.0 g of isopropanolamine were mixed, and then mixed with 6.0 g of nano-silver powder to prepare a nano-silver paste with a mass fraction of 60%. The mixture was kept warm in a water bath at 15° C., and the nano-silver paste was ultrasonically dispersed for 3 minutes using a cell wall disruptor for standby use.
[0061] 0.10 g of phorone and 0.40 g of n-octanoic acid were mixed, and then mixed with 10.0 g of main silver powder, and surface treated by planetary mechanical stirring before use.
[0062] 5g of treated main silver powder was mixed with 200μL of nano silver paste, and then sealed and stirred again by planetary mechanical stirring for 1min to obtain mixed silver paste. (The density of nano silver paste is about 2.0g / cm 3 , take 200 μL of nano-silver paste, which is approximately equal to 0.4 g of nano-silver paste, wherein the mass of nano-silver powder is approximately 0.24 g, and the mass ratio of nano-silver powder to main silver powder is approximately 4.8%, the same below).
[0063] The mixed silver paste is dried at 40° C. to obtain silver powder whose surface is modified by nano silver powder particles.
[0064] Example 2
[0065] 1.5 g of n-hexane and 2.5 g of isopropanolamine were mixed, and then mixed with 6.0 g of nano-silver powder to prepare a nano-silver paste with a mass fraction of 60%. The mixture was kept warm in a water bath at 15° C., and the nano-silver paste was ultrasonically dispersed for 3 minutes using a cell wall disruptor for standby use.
[0066] 0.10 g of phorone and 0.40 g of linoleic acid were mixed, and then mixed with 10.0 g of main silver powder, and surface treated by planetary mechanical stirring before use.
[0067] 5 g of the treated main silver powder was mixed with 200 μL of nano silver paste, and the mixture was sealed and subjected to planetary mechanical stirring for 1 min to obtain a mixed silver paste.
[0068] The mixed silver paste is dried at 40° C. to obtain silver powder whose surface is modified by nano silver powder particles.
[0069] Example 3
[0070] Mix 1.5g of n-hexane and 2.5g of ethanolamine, and then mix with 6.0g of nano-silver powder to prepare a nano-silver paste with a mass fraction of 60%. Keep it warm in a water bath at 15°C, use a cell wall disruptor to ultrasonically disperse the nano-silver paste for 3 minutes, and set aside.
[0071] Mix 0.10g of cyclohexanone and 0.40g of hexanoic acid, and then mix with 10.0g of main silver powder, and use planetary mechanical stirring to perform surface treatment, and then set aside.
[0072] 5 g of the treated main silver powder was mixed with 200 μL of nano silver paste, and the mixture was sealed and subjected to planetary mechanical stirring for 1 min to obtain a mixed silver paste.
[0073] The mixed silver paste is dried at 40° C. to obtain silver powder whose surface is modified by nano silver powder particles.
[0074] Example 4
[0075] Mix 1.5g of triethylamine and 2.5g of ethanolamine, and then mix with 6.0g of nano-silver powder to prepare a nano-silver paste with a mass fraction of 60%. Keep it warm in a water bath at 15°C, use a cell wall disruptor to ultrasonically disperse the nano-silver paste for 3 minutes, and set aside.
[0076] Mix 0.10g of ethylene glycol and 0.40g of hexanoic acid, then mix with 10.0g of main silver powder, and use planetary mechanical stirring to perform surface treatment.
[0077] 5 g of the treated main silver powder was mixed with 200 μL of nano silver paste, and the mixture was sealed and subjected to planetary mechanical stirring for 1 min to obtain a mixed silver paste.
[0078] The mixed silver paste is dried at 40° C. to obtain silver powder whose surface is modified by nano silver powder particles.
[0079] Comparative Example 1
[0080] 4.0 g of n-hexane was mixed with 6.0 g of nano-silver powder to prepare a nano-silver paste with a mass fraction of 60%, and the mixture was kept warm in a water bath at 15° C. The nano-silver paste was ultrasonically dispersed for 3 min using a cell wall disruptor and set aside.
[0081] 0.10 g of ethylene glycol and 0.40 g of hexanoic acid were mixed, and then mixed with 10.0 g of main silver powder, and surface treated by planetary mechanical stirring before use.
[0082] 5 g of the treated main silver powder was mixed with 200 μL of nano silver paste, and the mixture was sealed and subjected to planetary mechanical stirring for 1 min to obtain a mixed silver paste.
[0083] The mixed silver paste is dried at 40° C. to obtain silver powder whose surface is modified by nano silver powder particles.
[0084] Comparative Example 2
[0085] 1.5 g of n-hexane and 2.5 g of isopropanolamine were mixed, and then mixed with 6.0 g of nano-silver powder to prepare a nano-silver paste with a mass fraction of 60%. The mixture was kept warm in a water bath at 15° C., and the nano-silver paste was ultrasonically dispersed for 3 minutes using a cell wall disruptor for standby use.
[0086] Mix 0.5 g of phorone and then mix with 10.0 g of main silver powder, use planetary mechanical stirring to perform surface treatment, and set aside.
[0087] Step 3: Mix 5 g of the treated main silver powder with 200 μL of nano silver paste, seal and perform planetary mechanical stirring for 1 min to obtain a mixed silver paste.
[0088] The mixed silver paste is dried at 40° C. to obtain silver powder whose surface is modified by nano silver powder particles.
[0089] The powders of Examples 1-3 and the main silver powder without surface modification were pressed into tablets and sintered at 150°C. The resistance at both ends of the sintered samples was then tested using a multimeter. The three-dimensional dimensions of the samples were measured and the bulk resistivity was calculated as shown in Table 1 below.
[0090] Table 1 Volume resistivity data of untreated silver powder and samples prepared in Examples 1-3
[0091] <![CDATA[Tablet volume (cm 3 )]]> Tablet mass (g) <![CDATA[Tabletting density (g / cm 3 )]]> Volume resistance (ohm*m) Untreated silver powder 0.0880 0.5673 6.5783 <![CDATA[5.083×10 -6 ]]> Example 1 0.0859 0.5844 6.8057 <![CDATA[4.931×10 -7 ]]> Example 2 0.0850 0.5965 6.9819 <![CDATA[7.580×10 -7 ]]> Example 3 0.0812 0.5616 6.9159 <![CDATA[4.931×10 -7 ]]> Comparative Example 1 0.0932 0.5701 6.117 <![CDATA[7.955×10 -6 ]]> Comparative Example 2 0.0897 0.5608 6.252 <![CDATA[5.726×10 -6 ]]>
[0092] According to the data in Table 1, combined Figure 1-4 After the surface modification of the main silver powder, the volume resistance of the sample obtained by the present invention is significantly reduced, which shows that the modification effect of the present invention on the silver powder is good. Thermomechanical analysis (TMA) is performed on it, and it is found that the shrinkage rate is significantly reduced and the tap density is significantly improved, which is better than the silver powder tablets after ordinary treatment. The resistance is greatly reduced and the conductive performance is enhanced by testing the resistance with a multimeter.
[0093] Combination Figure 1-3 The silver powder obtained by the treatment of the present invention shows under a scanning electron microscope that most of the nano-silver powder is filled in the particle gaps of the main silver powder. The main silver powder is spherical silver powder with holes on the surface, and some of the nano-silver powder is embedded in the holes. Some of the nano-silver powder is connected to the main powder through the added organic solvent to achieve "bridging". The coated organic matter makes the main silver powder and the nano-silver powder bond to each other, and reduces the sintering temperature during the sintering process, thereby reducing the required sintering temperature.
[0094] The embodiments provided by the present invention are described in detail above. Specific examples are used herein to describe the principles and implementation methods of the present invention, and the description of the above embodiments is only used to help understand the core idea of the present invention. It should be pointed out that for ordinary technicians in this technical field, without departing from the principles of the present invention, the present invention can also be improved and modified in a number of ways, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A method for surface modification of silver powder, It is characterized in that Here are the steps: (1) mixing a first low boiling point solvent with a high boiling point alcoholamine compound to form a first organic solvent, and mixing a second low boiling point solvent with a high boiling point carboxylic acid compound to form a second organic solution; (2) mixing the first organic solvent with the nano silver powder and performing ultrasonic dispersion to form a nano silver paste; (3) mixing the second organic solvent with the main silver powder so that the surface of the main silver powder is wetted by the second organic solvent; (4) mixing the nano silver paste and the wetted main silver powder evenly to obtain a mixed silver paste; (5) Drying the mixed silver paste to obtain surface-modified silver powder.
2. The method for surface modification of silver powder according to claim 1, It is characterized in that In the first organic solvent, the first low boiling point solvent is an organic solvent having a boiling point of 50 to 100° C., and the boiling point of the alcoholamine compound is 150 to 200° C.; The mass ratio of the first low boiling point solvent to the alcohol amine compound is (0.2-0.8):
1.
3. The method for surface modification of silver powder according to claim 2, It is characterized in that The first low boiling point solvent includes one or more of n-hexane, triethylamine, methanol and acetone.
4. The method for surface modification of silver powder according to claim 2, It is characterized in that The alcoholamine compound includes one or more of ethanolamine, isopropanolamine, N-methylethanolamine, and aminomethylpropanol.
5. The method for surface modification of silver powder according to claim 1, It is characterized in that In step (2), the mass ratio of nano silver powder to nano silver paste is (0.6-0.8):
1.
6. The method for surface modification of silver powder according to claim 1, It is characterized in that In the second organic solvent, the second low boiling point solvent is an organic solvent with a boiling point of 100 to 200° C., the boiling point of the carboxylic acid compound is 140 to 300° C., preferably, the boiling point of the carboxylic acid compound is 200 to 300° C.; The mass ratio of the second low boiling point solvent to the carboxylic acid compound is (0.2-0.8):
1.
7. The method for surface modification of silver powder according to claim 6, It is characterized in that The second low boiling point solvent includes one or more of phorone, cyclohexanone and ethylene glycol.
8. The method for surface modification of silver powder according to claim 6, It is characterized in that The carboxylic acid compound includes one or more of acrylic acid, n-octanoic acid, linoleic acid, and caproic acid.
9. The method for surface modification of silver powder according to claim 1, It is characterized in that In step (3), the main silver powder is silver powder with a D50 particle size of 1 to 2 μm.
10. The method for surface modification of silver powder according to claim 1, It is characterized in that The mass ratio of the second organic solvent to the main silver powder is (0.001-0.05):1.
